Medicine in ophthalmology. (December 2018) - Heng, L.Z.; Hamilton, Robin D.
Abstract: Ophthalmology is often a branch of medicine that is viewed as minor in relation to other specialities. However, there are numerous ophthalmic manifestations of neurological, rheumatological and general medical conditions. Some of these are considered emergencies (see pages xx of this chapter), but often signs are found within the eye that lead to systemic diagnoses requiring further intervention.